Cash Receipt Information System at Rainbow Boarding House - Gowasa, Krismas; Rahmi, Elvika; Lumbanbatu, Maristella J. (SEAN Institute, 2022)
This research aims to enhance the efficiency and accuracy of financial management in boarding houses by designing and implementing a Cash Receipt Information System. Kos Rainbow is selected as a case study due to the complexity of managing cash receipts from various sources, such as room rent, additional services, and deposits. The research methodology includes system requirement analysis, database design, application development, and implementation testing. Data obtained from interviews with the boarding house owner, direct observation, and documentation will be utilized to design a system tailored to specific needs. Anticipated benefits include improved time efficiency, reduced potential for human errors in cash receipt recording, and providing the boarding house owner with more accurate and real-time financial information for more timely decision-making. The implementation of this cash receipt information system is expected to create better financial governance, enhance the quality of services to boarders, and assist boarding house owners in making strategic decisions related to financial management.